2020
DOI: 10.1111/iej.13266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transforming growth factor‐β1 on plasminogen activation in stem cells from the apical papilla: role of activating receptor‐like kinase 5/Smad2 and mitogen‐activated protein kinase kinase (MEK)/extracellular signal‐regulated kinase (ERK) signalling

Abstract: of transforming growth factor-b1 on plasminogen activation in stem cells from the apical papilla: role of activating receptorlike kinase 5/Smad2 and mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…The higher concentrations of TGF‐β1 (5 and 10 ng mL −1 ) generated significantly more deteriorating effects to cells than the lower concentrations. The findings correlate with a previous study showing that SCAP cultured in the presence of TGF‐β1 had less cell viability, and the use of high concentration (10 ng mL −1 ) generated the negative effect (19). Similar to earlier studies that reported the cytostatic effect of TGF‐β1 on various mammalian cells via various pathways, including the suppression of several key transcription factors regulating growth and the expression of cyclin‐dependent kinase (CDK) inhibitor (24,25).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The higher concentrations of TGF‐β1 (5 and 10 ng mL −1 ) generated significantly more deteriorating effects to cells than the lower concentrations. The findings correlate with a previous study showing that SCAP cultured in the presence of TGF‐β1 had less cell viability, and the use of high concentration (10 ng mL −1 ) generated the negative effect (19). Similar to earlier studies that reported the cytostatic effect of TGF‐β1 on various mammalian cells via various pathways, including the suppression of several key transcription factors regulating growth and the expression of cyclin‐dependent kinase (CDK) inhibitor (24,25).…”
Section: Discussionsupporting
confidence: 90%
“…Promising results were consistently reported showing cell viability improvement and cell differentiation (17,18). Moreover, a recent study proposed that TGF‐β1 might affect the repair/regeneration activities of stem cells from apical papilla (SCAP) via ALK5/Smad2/3 and MEK/ERK activation (19).…”
Section: Introductionmentioning
confidence: 99%
“…81 Chang et al showed that TGF-b stimulates PAI-1 and suPAR secretion in a system of repair/regeneration activities of stem cells from apical papilla (SCAP). 82 Besides a widespread thrombosis in patients with COVID-19, the examination of the lung during an autopsy of 7 deceased COVID-19 patients also demonstrated increased angiogenesis. 76 Recent evidence has revealed higher vascular endothelial growth factor (VEGF) levels in COVID-19 patients than in healthy controls.…”
Section: Angiogenesis and Coagulationmentioning
confidence: 96%
“…Chang et al . showed that TGF‐β stimulates PAI‐1 and suPAR secretion in a system of repair/regeneration activities of stem cells from apical papilla (SCAP) 82 …”
Section: Involvement Of Tgf‐β In Different Pathogenesesmentioning
confidence: 99%
“…SCAPs can differentiate into radicular pulp as well as the odontoblasts that are responsible for root dentinogenesis, and undergo morphological and functional changes. These postnatal stem cells play a crucial role in pulp-dentine complex healing and regeneration when the roots of young permanent teeth are damaged (Chang et al, 2020). A greater understanding of the cellular and molecular mechanisms that regulate human SCAPs (hSCAPs) activity is likely to improve tooth tissue engineering.…”
Section: Introductionmentioning
confidence: 99%